Temporal analysis of the reduction in gas emission in areas of mechanically-harvested sugarcane using satellite imagery - Arraes, Christiano Luna [UNESP]; Camacho-Tamayo, Jesus; Pissarra, Teresa Tarle; Bueno, Celia P. [UNESP]; Campos, Sergio [UNESP] (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2010)
The primary objective of this study was to estimate the amount of gas not emitted into the air in areas cultivated with sugarcane (Saccharum officinarum) that were mechanically harvested. Satellite images CBERS-2/CCD, from 08-13-2004, 08-14-2005, 08-15-2006 and 08-16-2007, of northwestern São Paulo State were processed using the Geographic Information System (GIS)-IDRISI 15.0. Areas of interest (the mechanically-harvested sugarcane fields) were identified and quantified based on the spectral response of the bands studied. Based on these data, the amount of gas that was not emitted was evaluated, according to the estimate equation proposed by the Intergovernmental Panel on Climate Change (IPCC). The results of 396.65 km(2) (5.91% for 2004); 447.56 km(2) (6.67% for 2005); 511.54 km(2) (7.62% in 2006); and 474.60 km(2) (7.07% for 2007), calculated from a total area of 6,710.89 km(2) with sugarcane, showed a significant increase of mechanical harvesting in the study area and a reduction of gas emissions of more than 300,000 t yr(-1).

Este trabajo tuvo por objetivo estimar temporalmente la cantidad de gases que dejaron de ser emitidos al aire, en áreas cultivadas con caña de azúcar (Saccharum offcinarum), cosechadas mecánicamente, en el noroeste del Estado de São Paulo utilizando imágenes orbitales. Se utilizaron cuatro imágenes del satélite CBERS-2/CCD, con recepción los días 13/08/2004; 14/08/2005; 15/08/2006 e 16/08/2007, donde se procesó por medio del Sistema de Información Geográfca (SIG) IDRISI 15.0. Fue posible, por medio de la clasifcación supervisada, identifcar y cuantifcar las áreas de interés (caña cosechada mecánicamente) debido a las respuestas espectrales de las bandas estudiadas. Con base en estos datos, se valoró la cantidad de gases dejados de emitir, de acuerdo a la estimación propuesta por la Intergovernmental Panel on Climate Change (IPCC). Estas áreas calculadas corresponden a 396,65 km2 (5,91% para el 2004), 447,56 km2 (6,67% para el 2005); 511,54 km2 (7,62% para el 2006) y 474,60 km2 (7,07% para el 2007), de un total de 6710,89 km2 con caña de azúcar, presentando un aumento signifcativo de la cosecha mecanizada y reducción de emisión de gases de efecto invernadero, superior a 300.000 t año-1, para la zona de estudio.
Análisis temporal de reducción de emisión de gases en áreas de caña de azúcar cosechadas mecánicamente utilizando imágenes satelitales
Keywords: Geographic information system; orbital image; Remote sensing; Saccharum officinarum